PERAN KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU: indonesia - ABDI SETIAWAN; Tajudin Noor; Sayan Suryana (LPPM STIT PRINGSEWU, 2021)
Abstract This study aims to analyze and illustrate the leadership role of the madrasa head in improving teacher performance in MIS Asy Syarifiyah, Cikampek District, Karawang Regency. The study uses descriptive qualitative research methods. Data collection is done by using methods a) observation, b) interviews and c) documentation. Based on the results of the study it can be concluded that the headmaster of the madrasa uses a democratic leadership style and has performed its role as a madrasa leader in improving teacher performance by making plans and implementation through coaching and development. So that between leadership and planning styles as well as the implementation of the headmaster has a causal relationship or cause and effect that makes the teacher as a professional educator to realize the objectives of the madrasah better. Keywords: Role of Leadership, Teacher Performance.